Using Kotobee Author Software to Design Integrated Topic E-books and Using them in Teaching Chemisitry - Thi Thu Hoai, Vu (VNU Journal of Science: Education Research, 2019)
At present, with the development of computer science and in the context of the fourth industrial revolution, technology products are used in all fields. In the field of education, more and more pieces of software and applications that support teaching are created, and one of them is e-books. E-books are documents which can flexibly and efficiently provide students with information and instructions in the form of multimedia and therefore can support and improve learning. The article presents the process of using Kotobee Author software to build e-book contents and using e-books to teach integrated topics in teaching chemistry with a view to developing self-learning ability for students.